Methodological Study to Develop Standard Operational Protocol on Intravenous (IV) Drug Administration For Children and to Assess its Implication - Bijarania, Sunil Kumar; Saini, Sushma Kumari; Verma, Sanjeev (Journal of Nepal Paediatric Society, 2018)
Introduction: Medicine administration forms a major part of the registered nurse’s role. Medicines are prescribed by a physician and dispensed by the pharmacist but responsibility for correct administration rests with the registered nurse. Fatal consequences have been noted following wrong drug, dose, diluent and unsterile technique. The objective of this study was to develop standard operational protocol (SOP) on Intravenous (IV) drug administration and checklist to assess the implementations of the developed SOP. Material and Methods: A methodological research design was adapted to carry out the study. Medicine wards (4-B, 4-C, 5-B and 5-C), Emergency room, PICU at Advanced Paediatric Centre (APC) of Post Graduate Institute of Medical Education and Research (PGIMER), Chandigarh. Thirty observations of IV drug administration and 58 bedside nurses working during July- September 2015. A prospective methodological study was performed to generate SOP. Total 17 FGDs were conducted and data was analysed with SPSS (Version-20.0). Results: The Content Validity Index (CVI) of SOP and checklist was 99.77% that means all items in both SOP and checklist are valid. Cronbach’s-alpha was calculated to assess Internal Consistency of checklists. Over-all standardized Cronbach’s alpha was calculated 0.94 that means all items in the checklist are internally consistent and contributing to the total reliability of the checklist. All the nurses felt that SOP is useful. Conclusion: Valid and feasible SOP for drug administration to children through IV route along with valid and reliable checklist was developed. It is recommended to use this document for drug administration for children.